Diaphragm, preparation method thereof and nickel-metal hydride battery

The nickel-hydrogen cell separator is prepared by interleaving bacterial cellulose fibers and nanocellulose crystals, which solves the problem that the separator needs to be hydrophilized and easily pierced, and achieves high mechanical properties and good liquid absorption, reduces the preparation cost and improves the battery safety performance.

CN119890607APending Publication Date: 2025-04-25SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411903158.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The nickel-hydrogen battery separators require hydrophilic treatment and are easily punctured, resulting in high production cost and insufficient safety performance.

Method used

The diaphragm is prepared by interwoven bacterial cellulose fibers (BC) and nanocellulose crystals (CNC). The mechanical properties are improved through hydrogen bonding, and the hydroxyhydrophilic groups and sulfonic acid groups of the nanocellulose crystals provide good liquid absorption and self-discharge inhibition effect.

Benefits of technology

The excellent mechanical properties and good liquid absorption of the diaphragm are achieved, the preparation process and cost are reduced, and the safety performance and cycle life of the nickel-hydrogen battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a diaphragm, a preparation method thereof and a nickel-metal hydride battery, the diaphragm comprises bacterial cellulose fibers (BC) and nano cellulose crystals (CNC), and the mass ratio of the bacterial cellulose fibers to the nano cellulose crystals is (7-8): (2-3). The diaphragm is formed by interweaving the bacterial cellulose fibers and the nano cellulose crystals, and strong hydrogen-bond interaction exists among bacterial cellulose fiber molecules, among nano cellulose crystal molecules and among bacterial cellulose fiber molecules and nano cellulose crystal molecules, so that the diaphragm is endowed with excellent mechanical properties by the hydrogen bonds; the anti-puncture requirement can be met even if the thickness is low, so that the application in a high-capacity nickel-metal hydride battery is realized, and the safety performance of the anti-puncture nickel-metal hydride battery is improved. Meanwhile, a large number of hydroxyl hydrophilic groups on the nanocellulose crystals provide good liquid absorption for the diaphragm, and the diaphragm can still keep high liquid retention capacity after extrusion, so that additional hydrophilization treatment is not needed, the preparation procedures are reduced, and the manufacturing cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nickel-hydrogen batteries, and in particular to a diaphragm and a preparation method thereof, and a nickel-hydrogen battery. Background Art

[0002] With the continuous development of science and technology, electronic devices have higher and higher requirements for battery performance. As a high-performance secondary battery, nickel-hydrogen batteries have the advantages of high specific energy, long cycle life and good safety, so they have been widely used in many fields. However, the performance of nickel-hydrogen batteries depends to a large extent on the performance of their diaphragms. As an important component of nickel-hydrogen batteries, the diaphragm not only plays a role in physically isolating the positive and negative electrodes to avoid battery short circuits, but also significantly affects the key performance of the battery, such as internal resistance, capacity, self-discharge and cycle life.

[0003] At present, polyolefin fibers are the main raw materials for nickel-metal hydride battery separators. However, since there are no hydrophilic groups in the molecular chain, hydrophilic treatments such as grafting modification, sulfonation or surfactant treatment are required when using them in nickel-metal hydride battery separators, which increases the preparation process and manufacturing cost of the separator. In addition, thin separators used with high-capacity batteries are easily punctured due to their poor mechanical properties, posing the risk of battery short circuit. Summary of the invention

[0004] The embodiments of the present invention provide a diaphragm and a preparation method thereof, and a nickel-hydrogen battery, so as to solve the problem that the diaphragm needs to be hydrophilized and is easily punctured, thereby achieving the effect of reducing costs and improving safety performance.

[0005] Specifically, the present invention provides a membrane comprising bacterial cellulose fibers (BC) and nanocellulose crystals (CNC), wherein the mass ratio of the bacterial cellulose fibers to the nanocellulose crystals is (7-8): (2-3).

[0006] Optionally, the bacterial cellulose fiber has a diameter of 2nm-4nm and a length of 80mm-120mm.

[0007] Optionally, the nanocellulose crystals have a diameter of 5nm-50nm and a length of 100nm-500nm.

[0008] Optionally, the aspect ratio of the bacterial cellulose fibers is 20,000-60,000, and the aspect ratio of the nanocellulose crystals is 20-100.

[0009] Optionally, the mass of the diaphragm is 15g-50g per square meter.

[0010] The present invention also provides a method for preparing the diaphragm according to any one of the above items, comprising the following steps: Evenly dispersing the bacterial cellulose fibers and the nanocellulose crystals in deionized water to obtain a suspension; The suspension is subjected to dehydration, molding, pressing and drying processes to obtain the diaphragm.

[0011] Optionally, the sum of the concentration of the bacterial cellulose fibers in the deionized water and the concentration of the nanocellulose crystals in the deionized water is 0.2 wt %-4.0 wt %.

[0012] Optionally, the dispersion is carried out in a deflaking machine; wherein the deflaking speed is 2000-10000 rpm and the time is 3 min-15 min.

[0013] Optionally, the vacuum degree of the dehydration molding is 15kPa-40kPa; And / or, the vacuum degree of the pressing is 50 kPa-60 kPa; And / or, the drying temperature is 60° C.-90° C. and the drying time is 3 min-8 min.

[0014] The present invention also provides a nickel-hydrogen battery, characterized in that it comprises the diaphragm as described in any one of the above items.

[0015] The beneficial effects of the present invention are: In the diaphragm and nickel-hydrogen battery provided by the present invention, since the diaphragm is interwoven with bacterial cellulose fibers and nanocellulose crystals, there are strong hydrogen bonds between bacterial cellulose fiber molecules, between nanocellulose crystal molecules, and between bacterial cellulose fiber molecules and nanocellulose crystal molecules. These hydrogen bonds give the diaphragm excellent mechanical properties, so that it can meet the requirements of anti-puncture even at low thickness, thereby realizing the application in high-capacity nickel-hydrogen batteries and improving its safety performance. At the same time, the large number of hydroxyl hydrophilic groups on the nanocellulose crystals provide the diaphragm with good liquid absorption, and it can still maintain a high liquid retention capacity after extrusion, so there is no need for additional hydrophilization treatment, which not only reduces the preparation process, but also reduces the manufacturing cost.

[0016] Furthermore, the sulfonic acid groups on the nanocellulose crystals can capture redox shuttle substances such as nitrogen-containing compounds, thereby effectively inhibiting the self-discharge phenomenon of nickel-hydrogen batteries. DETAILED DESCRIPTION

[0017] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0018] An embodiment of the present invention provides a membrane, comprising bacterial cellulose fibers (BC) and nanocellulose crystals (CNC), wherein the mass ratio of the bacterial cellulose fibers to the nanocellulose crystals is (7-8): (2-3).

[0019] Since the diaphragm is interwoven with bacterial cellulose fibers and nanocellulose crystals, there are strong hydrogen bonds between bacterial cellulose fiber molecules, between nanocellulose crystal molecules, and between bacterial cellulose fiber molecules and nanocellulose crystal molecules. These hydrogen bonds give the diaphragm excellent mechanical properties, so that it can meet the requirements of anti-puncture even at low thickness, thereby realizing its application in high-capacity nickel-hydrogen batteries and improving its safety performance. At the same time, the large number of hydroxyl hydrophilic groups on the nanocellulose crystals provide the diaphragm with good liquid absorption, and it can still maintain a high liquid retention capacity after extrusion, so there is no need for additional hydrophilization treatment, which not only reduces the preparation process, but also reduces the manufacturing cost. Furthermore, the sulfonic acid groups on the nanocellulose crystals can capture redox shuttle substances such as nitrogen-containing compounds, thereby effectively inhibiting the self-discharge phenomenon of nickel-hydrogen batteries.

[0020] In one embodiment of the present invention, the diameter of the bacterial cellulose fiber is 2nm-4nm and the length is 80mm-120mm. Further, the diameter of the nanocellulose crystal is 5nm-50nm and the length is 100nm-500nm. The aspect ratio of the bacterial cellulose fiber is 20000-60000, and the aspect ratio of the nanocellulose crystal is 20-100.

[0021] In the embodiment of the present invention, the bacterial cellulose fiber is the overall skeleton of the diaphragm and mainly plays a supporting role. Nanocellulose crystals are mainly used to fill the large pores of the diaphragm to avoid direct contact between the positive and negative electrodes or reduce the risk of micro-short circuits in the battery. The compounding of two fibers of different sizes is beneficial to adjusting the pores of the diaphragm and improving the overall mechanical properties of the diaphragm. If the proportion of bacterial cellulose fibers is too high, it will result in too many pores on the diaphragm, relatively poor mechanical properties, and the risk of battery short circuit. If the proportion of bacterial cellulose fibers is too low, it will make the diaphragm difficult to form, or the mechanical properties after forming will be relatively poor.

[0022] In one embodiment of the present invention, the mass of the diaphragm per square meter is 15g-50g. If the mass of the diaphragm per square meter is high, the diaphragm will be too thick, increasing the length of the ion transmission path inside the battery, reducing the ion transmission efficiency, and thus reducing the power output capacity of the battery. If the mass of the diaphragm per square meter is low, the diaphragm will be too thin, resulting in insufficient mechanical strength and easy puncture during battery assembly or use.

[0023] The present invention also provides a method for preparing a diaphragm, comprising the following steps: Evenly dispersing the bacterial cellulose fibers and the nanocellulose crystals in deionized water to obtain a suspension; The suspension is subjected to dehydration, molding, pressing and drying processes to obtain the diaphragm.

[0024] Specifically, the sum of the concentration of the bacterial cellulose fiber in the deionized water and the concentration of the nanocellulose crystals in the deionized water is 0.2wt%-4.0wt%. The dispersion is carried out in a deflaking machine; wherein the deflaking speed is 2000-10000rpm and the time is 3min-15min. The vacuum degree of the dehydration molding is 15kPa-40kPa. The vacuum degree of the pressing is 50kPa-60kPa. The drying temperature is 60℃-90℃ and the time is 3min-8min.

[0025] The present invention is further described below by means of specific examples.

[0026] Example 1 Preparation of membrane: Weigh bacterial cellulose fiber (BC) and nanocellulose crystal (CNC) in a mass ratio of 7:3, add a certain amount of deionized water to make the concentration of BC and CNC reach 1.0 wt%. The diameter of bacterial cellulose fiber is 2nm and the length is 80mm. The diameter of nanocellulose crystal is 5nm and the length is 100nm. Use a high-speed decompressor to decompress it at 3000 rpm to evenly disperse it to obtain a BC / CNC mixed suspension. Press 20g / m 2 The suspension was weighed quantitatively and passed through a paper former under vacuum dehydration at 20 kPa to obtain a wet film. The water was further removed under vacuum pressing at 50 kPa to enhance the bonding force between fibers and improve the smoothness and mechanical strength of the separator. Finally, the BC / CNC composite separator with a thickness of 0.09 mm was obtained by drying at 70 °C for 5 min.

[0027] Preparation of positive electrode sheet: Add 1wt% TiO2, 1wt% Y2O3, 2wt% Yb2O3, and 0.1wt% methyl cellulose to deionized water and stir at 400rpm for 5min using a mechanical stirrer. Then add 93.9wt% cobalt-coated nickel balls and continue stirring at 400rpm for 60min. Finally, add 2wt% polytetrafluoroethylene and continue stirring for 5min to obtain positive electrode slurry. The positive electrode slurry is evenly coated on a surface density of 280 g / m 2 The positive electrode is placed on a nickel foam substrate and then dried and cut into positive electrode sheets of appropriate size.

[0028] Preparation of negative electrode sheet: Add 0.5wt% carboxymethyl cellulose, 1wt% sodium polyacrylate and 1wt% hydroxypropyl cellulose to deionized water, and stir at 400rpm for 5-10min using a mechanical stirrer. Then add alloy powder and continue stirring at 400rpm for 120min. Finally, add styrene-butadiene rubber and stir for 5-10min to obtain negative electrode slurry; the speed of mechanical stirring is 400-1000 rpm. After the negative electrode slurry is prepared, it is evenly coated on a punched nickel-plated steel strip substrate, and cut into negative electrode sheets of appropriate size after drying.

[0029] Preparation of electrolyte: 15.9 wt % KOH, 13.4 wt % NaOH and 1.7 wt % LiOH were added to deionized water and dissolved to obtain an electrolyte with a specific gravity of 1.28 g / mL and a concentration of 7.86-8.10 mol / L.

[0030] Preparation of nickel-hydrogen battery: The positive and negative electrodes and separators are wound, and then liquid is injected and sealed to assemble an AA-type nickel-hydrogen battery with a capacity of 2600 mAh.

[0031] Example 2 The only difference between this embodiment and embodiment 1 is that the mass ratio of bacterial cellulose fibers (BC) to nanocellulose crystals (CNC) is 8:2.

[0032] Example 3 The only difference between this embodiment and embodiment 1 is that the mass ratio of bacterial cellulose fibers (BC) to nanocellulose crystals (CNC) is 7.5:2.5.

[0033] Example 4 The difference between this embodiment and embodiment 1 is that: 2 The suspension is quantitatively weighed to obtain a BC / CNC composite separator with a thickness of 0.12 mm; and the coating amount on the positive and negative electrode sheets is appropriately adjusted, the positive and negative electrode sheets and the separator are wound, and then the liquid is injected and sealed to assemble an AA-type nickel-hydrogen battery with a capacity of 1900 mAh.

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that only bacterial cellulose fibers (BC) are used as raw materials, and nanocellulose crystals (CNC) are not used.

[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that only nanocellulose crystals (CNC) are used as raw materials, and bacterial cellulose fibers (BC) are not used.

[0036] Comparative Example 3 The only difference between this comparative example and Example 1 is that the mass ratio of bacterial cellulose fibers (BC) to nanocellulose crystals (CNC) is 6:4.

[0037] Comparative Example 4 The only difference between this comparative example and Example 1 is that the mass ratio of bacterial cellulose fibers (BC) to nanocellulose crystals (CNC) is 9:1.

[0038] Comparative Example 5 The only difference between this comparative example and Example 1 is that the diaphragm is a sulfonated diaphragm with a thickness of 0.09 mm in the prior art.

[0039] Comparative Example 6 The only difference between this comparative example and Example 1 is that the diaphragm is a fluorinated diaphragm with a thickness of 0.09 mm in the prior art.

[0040] Comparative Example 7 The only difference between this comparative example and Example 4 is that the diaphragm is a sulfonated diaphragm in the prior art.

[0041] Comparative Example 8 The only difference between this comparative example and Example 4 is that the diaphragm is a fluorinated diaphragm in the prior art.

[0042] Performance Testing 1. Basic performance of diaphragm: The BC / CNC composite diaphragm, sulfonated diaphragm and fluorinated diaphragm were tested for electrolyte wettability and mechanical properties.

[0043] Contact angle test: The diaphragm was first cut into discs with a diameter of 1.6 cm, and the contact angle was recorded using a surface contact angle tester, with the electrolyte drop volume being 5 μL.

[0044] Liquid absorption rate test: Cut the diaphragm into discs with a diameter of 1.6 cm, weigh its initial mass m0, soak it in electrolyte for 1 hour, wipe the surface with filter paper, and weigh its mass m1. The liquid absorption rate can be calculated by (m1-m0) / m0, and the average of the three measurement data is taken as the result.

[0045] Liquid absorption rate test after extrusion: Place the above-mentioned diaphragm after liquid absorption horizontally on a glass plate, and load 100 g weight on each disc for 10 min, weigh m2 again, and the liquid absorption rate after extrusion can be calculated by (m2-m0) / m0, and the average value of the three measurement data is taken as the result.

[0046] Liquid retention test after extrusion: calculated by liquid absorption after extrusion / liquid absorption.

[0047] Puncture strength test: The diaphragm is clamped on the sample fixture and punctured with a 0.08 mm probe to obtain the maximum penetration force.

[0048] The contact angle, liquid absorption rate, liquid absorption rate after extrusion, liquid retention rate after extrusion and puncture strength test results of the diaphragm are shown in Table 1: Table 1 Diaphragm performance test table It can be seen from Table 1 that the comprehensive performance of the diaphragms prepared in Examples 1-4 is better than that of the diaphragms in Comparative Examples 1-8, especially better than the sulfonated diaphragms and fluorinated diaphragms in the prior art. The reason is that there are strong hydrogen bonds between bacterial cellulose fiber molecules, between nanocellulose crystal molecules, and between bacterial cellulose fiber molecules and nanocellulose crystal molecules. These hydrogen bonds give the diaphragm excellent mechanical properties, so that it can meet the requirements of anti-puncture even at low thickness. In addition, the large number of hydroxyl hydrophilic groups on the nanocellulose crystals provide the diaphragm with good liquid absorption, and it can still maintain a high liquid retention capacity after extrusion.

[0049] Comparative Example 1 Compared with Examples 1-3, only bacterial cellulose fibers (BC) were used as raw materials, and nanocellulose crystals (CNC) were not used. Since the aspect ratio of bacterial cellulose fibers is relatively large, the structure of the prepared diaphragm is relatively loose, resulting in a small contact angle with the electrolyte. In addition, the porosity of the diaphragm is large, it is easy to be punctured, and the electrolyte absorbed therein is also easy to be squeezed out, so the liquid retention rate is low.

[0050] Comparative Example 2 Compared with Examples 1-3, only nanocellulose crystals (CNC) were used as raw materials, and bacterial cellulose fibers (BC) were not used. Since the aspect ratio of nanocellulose crystals is relatively small, the prepared diaphragm structure is relatively dense, resulting in a large contact angle of the electrolyte and not being easily punctured. However, it is more difficult for the electrolyte to enter the interior of the diaphragm, resulting in a decrease in the liquid absorption rate.

[0051] Compared with Examples 1-3, the proportion of nanocellulose crystals is increased in Comparative Example 3. As the proportion of nanocellulose crystals increases, the various properties of the separator gradually approach those of Comparative Example 2.

[0052] Compared with Examples 1-3, the proportion of bacterial cellulose fibers was increased in Comparative Example 4. As the proportion of bacterial cellulose fibers increased, the various properties of the diaphragm gradually approached those of Comparative Example 1.

[0053] 2. Performance of NiMH batteries: The NiMH batteries of Examples 1-4 and Comparative Examples 1-8 were subjected to charging tests and life tests.

[0054] The nickel-hydrogen batteries of Examples 1-3 and Comparative Examples 1-6 were formed according to Formation Method 1, and then subjected to a charge test according to Charge Test Method 1. The test results are shown in Table 2.

[0055] Formation method 1: (1) Charge at 260 mA for 10 hours, then discharge at 520 mA to 1.0 V; (2) Charge at 260 mA for 14 hours, then discharge at 520 mA to 1.0 V; (3) Charge at 260 mA for 16 hours, then discharge at 520 mA to 1.0 V.

[0056] Charge test method 1: (1) After formation, place for 30 seconds; (2) Charge at 260 mA for 16 hours and place for 30 seconds; (3) Discharge to 1.0 V at 520 mA and record the capacity; (4) Place at specified temperature (room temperature, 45°C or 60°C) for 28 days; (5) Charge at 260 mA for 16 hours and place for 30 seconds; (6) Discharge to 1.0 V at 520 mA and record the capacity.

[0057] Table 2 Charge test table 1 From Table 2, we can see that: From the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that adding nanocellulose crystals during the preparation of the diaphragm helps to improve the charging performance of the diaphragm battery. From the comparison between Example 1, Comparative Example 5 and Comparative Example 6, it can be seen that the battery assembled using the diaphragm prepared by the present invention has a better charging capacity than the battery assembled using the fluorinated or sulfonated diaphragm. The reason is that the nanocellulose crystals in the diaphragm of the present invention are evenly distributed, and the sulfonic acid groups on the nanocellulose crystals can capture redox shuttle substances such as nitrogen-containing compounds, thereby effectively inhibiting the self-discharge of the battery.

[0058] The nickel-hydrogen batteries of Example 4 and Comparative Examples 7 and 8 were formed according to Formation Method 2, and then subjected to a charge test according to Charge Test Method 2. The test results are shown in Table 3.

[0059] Formation method 2: (1) Charge at 190 mA for 10 hours, then discharge at 380 mA to 1.0 V; (2) Charge at 190 mA for 14 hours, then discharge at 380 mA to 1.0 V; (3) Charge at 190 mA for 16 hours, then discharge at 380 mA to 1.0 V.

[0060] Charge test method 2: (1) After formation, leave for 30 seconds; (2) Charge at 190 mA for 16 hours and leave for 30 seconds; (3) Discharge to 1.0 V at 380 mA, record the capacity and leave for 30 seconds; (4) Leave at specified temperature (room temperature, 45°C or 60°C) for 28 days; (5) Charge at 190 mA for 16 hours and leave for 30 seconds; (6) Discharge to 1.0 V at 380 mA and record the capacity.

[0061] Table 3 Charge test table 2 From Table 3, we can see that: The battery assembled with the diaphragm prepared by the present invention (Example 4) has better charging capacity than the battery assembled with the fluorinated or sulfonated diaphragm (Comparative Examples 7-8). The reason is that the nanocellulose crystals are evenly distributed in the diaphragm of the present invention, and the sulfonic acid groups on the nanocellulose crystals can capture redox shuttle substances such as nitrogen-containing compounds, thereby effectively inhibiting the self-discharge of the battery.

[0062] The nickel-hydrogen batteries of Examples 1-3 and Comparative Examples 1-6 were subjected to cycle tests according to cycle test method 1. The test results are shown in Table 4.

[0063] Cycle test method 1: Charge at 1900 mA for 1.1 hours, let stand for 30 seconds, then discharge at 1900 mA to 1.0 V; repeat the above charge and discharge test until the battery capacity decays to 60% of the first discharge capacity. Record the battery capacity after each cycle test.

[0064] Table 4 Cyclic test table 1 From Table 4, we can see that: From the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that adding too much nanocellulose crystals will lead to a dense diaphragm structure, a large electrolyte contact angle, and a low liquid absorption rate, which will affect the transmission of ions during charging and discharging, and the battery performance will be manifested as a large internal resistance and low capacity. Adding too much nanocellulose crystals will lead to a loose diaphragm structure and a low liquid holding rate after extrusion, and the battery performance will be manifested as a fast capacity decay and poor cycle life.

[0065] From the comparison between Example 1, Comparative Example 5 and Comparative Example 6, it can be seen that the battery assembled with the diaphragm prepared in the embodiment of the present invention exhibits a longer cycle life than the battery assembled with the commonly used sulfonated / fluorinated diaphragm. This is mainly due to the excellent electrolyte wettability of the BC / CNC diaphragm, which effectively reduces the electrolyte loss caused by the positive electrode squeezing the diaphragm during the battery cycle. In addition, its excellent mechanical strength allows it to maintain stable performance even at low thickness, providing a solid guarantee for the application of high-capacity batteries.

[0066] The nickel-hydrogen batteries of Example 4 and Comparative Examples 7-8 were subjected to cycle tests according to cycle test method 2. The test results are shown in Table 5.

[0067] Cycle test method 2: Charge at 1900 mA for 1.1 hours, let stand for 30 seconds, then discharge at 1900 mA to 1.0 V; repeat the above charge and discharge test until the battery capacity decays to 60% of the first discharge capacity. Record the battery capacity after each cycle test.

[0068] Table 5 Cyclic test table 2 From Table 5, we can see that: The battery assembled with the diaphragm prepared by the embodiment of the present invention (Example 4) shows a longer cycle life compared with the battery assembled with the commonly used sulfonated / fluorinated diaphragm (Comparative Examples 7-8). This is mainly due to the excellent electrolyte wettability of the BC / CNC diaphragm, which effectively reduces the electrolyte loss caused by the positive electrode squeezing the diaphragm during the battery cycle. In addition, its excellent mechanical strength allows it to maintain stable performance even at low thickness, providing a solid guarantee for the application of high-capacity batteries.

[0069] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.

Claims

1. A diaphragm, characterized in that: It comprises bacterial cellulose fibers and nanocellulose crystals, wherein the mass ratio of the bacterial cellulose fibers to the nanocellulose crystals is (7-8): (2-3).

2. The diaphragm according to claim 1, characterized in that The bacterial cellulose fibers have a diameter of 2nm-4nm and a length of 80mm-120mm.

3. The diaphragm according to claim 1, characterized in that The diameter of the nanocellulose crystal is 5nm-50nm and the length is 100nm-500nm.

4. The diaphragm according to claim 2 or 3, characterized in that: The aspect ratio of the bacterial cellulose fiber is 20000-60000, and the aspect ratio of the nanocellulose crystal is 20-100.

5. The diaphragm according to claim 1, characterized in that The mass of the diaphragm is 15g-50g per square meter.

6. A method for preparing a diaphragm according to any one of claims 1 to 5, characterized in that: The following steps are involved: Evenly dispersing the bacterial cellulose fibers and the nanocellulose crystals in deionized water to obtain a suspension; The suspension is subjected to dehydration, molding, pressing and drying processes to obtain the diaphragm.

7. The preparation method according to claim 6, characterized in that: The sum of the concentration of the bacterial cellulose fibers in the deionized water and the concentration of the nanocellulose crystals in the deionized water is 0.2 wt % to 4.0 wt %.

8. The preparation method according to claim 6, characterized in that: The dispersion is carried out in a deflaking machine, wherein the deflaking speed is 2000-10000 rpm and the time is 3 min-15 min.

9. The preparation method according to claim 6, characterized in that: The vacuum degree of the dehydration molding is 15kPa-40kPa; And / or, the vacuum degree of the pressing is 50 kPa-60 kPa; And / or, the drying temperature is 60° C.-90° C. and the drying time is 3 min-8 min.

10. A nickel-metal hydride battery, characterized in that: The invention comprises the diaphragm according to any one of claims 1 to 5.